PENGUJIAN EKSPERIMENTAL UNTUK MEMPELAJARI KARAKTERISTIK GETARAN PADA MODEL ROTOR GANDA KIT MENGGUNAKAN ANALISIS PETA SPEKTRUM DAN ORBIT - Noor Edy Edy (Jurnal Ilmiah Teknik Mesin POROS, 2021)
In modern technology, vibration signal is to be utilized in predictive maintenance application,more often when Dynamic Signal Analyzer (DSA) is invented. Unballance in rotor cause significantdeflection on rotated shaft and possible damage the machine. DSA is used in monitoring a condition ofbig rotation machines such as turbin, compressor, pump and generator. This research used double rotorsshaft system which was supported with journal bearing as a modification from the real rotation machines.Two of vibration characteristic as a sign of abnormal condition in rotation machine are unballance andoil whirl phenomenon. Meanwhile, oil whirl is seen in many rotation machines that use journal bearingas support its shaft. For rotation machine with high speed, oil whirl phenomenon can cause resonance inthe system, and then become the oil whip. Based on this condition that is very reasonable for makingearly detection, identification, and looking for the solution to prevent not wanted incident.